A CASE OF RENAL DISEASE IN HIV INFECTED PATIENT - Ni Made Vina Septiani; I Wayan Sudhana (Universitas Udayana, 2013)
Kidney diseases in human immunodeficiency virus (HIV) infected patients has been been fourth leading cause of death after sepsis, pneumonia, and liver disease. HIV-associated nephropathy (HIVAN) is the most common. We report a case, a male patient, 48 years, who experienced shortness of breath, cough and intermittent fever and has been reported as HIV positive, without previous antiretroviral treatment and last CD4+ count is 89 cells/mm3. There are elevated BUN and SC from day to day during treatment and proteinuria +2 as a sign of kidney disease with normal blood pressure and there was no edema. Patients given an antibiotic and ACE inhibitors as antiproteinuria. Patients with suspicion of HIVAN in this case can progress very rapidly and causes progressive decline in renal function. Prognosis of patients with HIVAN if not handled properly will develop end stage renal disease (ESRD) in 1-4 months and had a mortality rate 4.7 times higher than HIV patients without renal impairment.